Antibiotic Prescribing Pattern in Paediatric Emergency Department at Tertiary Care Teaching Hospital in Nepal - Yadav, Chandrajeet Kumar; Bishunke, Ravi; Shrivastava, Amit Kumar; Palikhey, Anjan; Chaurasia, Lokeshwar (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: The indiscriminate use of antibiotics often results in an increased incidence of adverse drug reactions (ADR), suboptimal therapy, treatment failure, polypharmacy and most importantly, the emergence of antibiotic resistance. Thus, the objective of this study was to assess the paediatric emergency department, antibiotic prescribing pattern at a tertiary care teaching hospital, Universal College of Medical Sciences (UCMS), Bhairahawa, Rupandehi, Nepal. Material and methods: A prospective, cross-sectional, observational study was carried out on 152 paediatric patients of ages between 2 months to 12 years at the paediatric emergency department of UCMS. The data were collected by reviewing the prescription paper, and the required information was recorded using a structured data collection sheet prepared for study. The prescribing pattern was assessed through the World Health Organization (WHO) prescription indicators using the WHO Children Formulary 1993 AD. Results: This study revealed that out of 152 patients, average number of drugs prescribed was 5.13 and antibiotic per patient was 2.10±.540. Antibiotics were prescribed at least once for 93.4% of patients. Drugs prescribed from Essential drug list (EDL) was 46.46% and that encountered with injectable was 92.1%. There was a significant difference between the patients age group and the number of drugs prescribed (χ2 = 21.553, p = 0.010). The mean duration of antibiotic treatment was 6.95±3.145. Cephalosporin’s (36.6%) followed by aminoglycosides (28.8%) were most frequently prescribed antibiotics. Conclusion: Multiple courses of antibiotics are most frequently prescribed, which could increase antibiotic resistance in future. Continuous audits, training and new treatment protocols should be developed for prescribing and using antibiotics in paediatric patients.